Conflict, inclusivity, and transformation of the rice value chain in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
This study explores the transformation of Myanmar’s rice value chain (VC) over a period of liberalization, reform, and infrastructure expansion from 2013 to 2019, and over a period of multiple crises from 2020 to 2022 including a military coup and widespread conflict. We analyze modernization over these periods at different levels of the VC, including upstream (farms), midstream (mills), and downstream (rice vendors). We rely upon unique data from large-scale phone surveys collected at different segments of the rice value chain – including farm and post-farmgate – complemented with insights from key informant interviews, and secondary data. The major findings are the following: 1. There have been large transformations within the rice value chain over the last decade, but modernization in some areas decelerated due to conflict. We note a process of modernization, upscaling, quality improvements, and increased outsourcing of agricultural activities to specialized service providers by farmers. The majority of this transformation occurred during the period of relative stability from 2013 to 2019. We show that although modernization continued during the crisis years that followed, including an improvement in rice quality and an expansion of modern mills, many modernization processes decelerated. Mills and farms in insecure and conflict-affected areas participated to a lesser extent and the modernization gaps widened during the crisis years. 2. Local rice market conditions improved with better-quality rice sold locally. A large share of food vendors indicated better rice quality overall at the time of survey compared to 3 and 10 years earlier. Sixty-eight percent of vendors reported that there was no foreign matter in the rice that they sold a decade ago. That share has increased by 23 percentage points to 91 percent in 2022. In domestic retail, modern retail is (yet) negligible in rice distribution at the national level. 3. Rice exports quadrupled, with Myanmar becoming globally the 5th biggest exporter of rice by the end of 2019. Rice exports have proven to be resilient during the crisis years. Rice exports increased dramatically despite more stringent, and costly, non-tariff measures for exports such as phyto-sanitary requirements. Rice is exported through different channels, moving away from low-quality rice trucked to China, to relatively better-quality and often certified rice being shipped on large vessels to a more diverse set of countries. We see shifting challenges over time – due to banking, electricity, and mobility problems that millers and traders adjusted to, at an increasing cost – but national exports mostly stabilized, in the crisis years compared to the period before, seemingly as major rice producing areas - except Sagaing - were less affected by conflicts, 4. Midstream, we see rapid uptake and investments in modern drying machines – especially mechanized dryers – and modern milling machinery in the form of new mill starts and upgrading from traditional mills. The average number of modern mills operating in the miller’s same village tract/ward increased by about 60 percent from 2013 to 2019 and by a further 10 percent in 2022. The trend for traditional mills is the opposite: declining by 50 percent between 2013 and 2019 and a further 15 percent in 2022. This modernization has been driven by local firm investments as Foreign Direct Investment (FDI) has been limited. 5. Upstream (at the farm level), we note a substantial expansion of modern input use. Rice seed markets have become more active in the 2010s. The sale of branded rice seeds doubled over the last decade. Chemical fertilizer use also increased over the last decade. While use was lower in 2022 than before the crisis, they were still at a higher level than a decade earlier. We also see increased use of modern harvest and post-harvest technologies and more outsourcing of harvest and post-harvest activities, mostly linked to these modern technologies and practices. In 2022, 54 percent of the farmers reported to have used a combine-harvester on most rice plots. Farmers hiring in tractors increased by 33 percentage points over the last decade. Outsourcing drying services has also increased, but the growth has been more modest: 22 percent of the farmers indicated that they outsourced the drying of paddy. Modern dryer use increased accordingly. 6. We find significant negative relationships between severe local conflict and many modernization outcomes. Severe conflict is found to negatively impact various modernization aspects, notably the adoption of tractor services and modern dryers at the farm level, and the prevalence of modern mills and drying equipment in midstream operations. 7. Modernization has not been everywhere inclusive. More remote and smaller firms are participating less in modern practices. More remote farmers show smaller growth in adoption of combine harvesters, modern dryers, and modern mills, while smaller farmers have smaller growth in the use of combine harvesters and drying service providers. In the midstream, mills in remote areas show smaller changes in the share of modern mills in their areas, while smaller mills have significantly slower growth in modern service provision and lower investment rates in value-added machinery. For many of these modernization outcomes, the gaps across firm size and remoteness widened during the crisis years.